Simulation and evaluation of hemodynamic characteristics of carotid blood flow in the process of aneurysm formation - D. A. Baliuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The final element method was used in the hemodynamic large vessel blood flow simulation (as part of the FlowVision program). The bloodstream geometry influence on its hemodynamic modification was studied.